Dampak Pandemi Covid - 19 Terhadap Efektivitas Penyelenggaraan Pendidikan Di Indonesia - Zainab Canu (IAIN Ternate, 2022)
The social distancing policy carried out by the government to prevent the transmission of the virus makes learning to be carried out from home by utilizing communication and information technology, or what is known as